2013
DOI: 10.1371/journal.pone.0076914
|View full text |Cite
|
Sign up to set email alerts
|

The MET13 Methylenetetrahydrofolate Reductase Gene Is Essential for Infection-Related Morphogenesis in the Rice Blast Fungus Magnaporthe oryzae

Abstract: Methylenetetrahydrofolate reductases (MTHFRs) play a key role in the biosynthesis of methionine in both prokaryotic and eukaryotic organisms. In this study, we report the identification of a novel T-DNA-tagged mutant WH672 in the rice blast fungus Magnaporthe oryzae, which was defective in vegetative growth, conidiation and pathogenicity. Analysis of the mutation confirmed a single T-DNA insertion upstream of MET13, which encodes a 626-amino-acid protein encoding a MTHFR. Targeted gene deletion of MET13 result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…Similarly, for Moarg1, Moarg5,6, and Moarg7, when conidia had been pre-incubated in arginine solution before the plant inoculation assays, exogenous arginine could partially restore the infection defects in appressorial penetration and invasive hyphae growth. The Moarg1, Moarg5,6, and Moarg7 mutants were able to penetrate plant leaf cuticles, but the penetration rate and invasive growth were obviously reduced compared with the wild type, which just like Momet13 and Molys2 mutants of M. oryzae (Yan et al, 2013;Chen et al, 2014). However, studies in str3 (methionine auxotrophy) and Moilv1 (isoleucine auxotrophy) showed that there was no statistical difference in penetration rate between mutants and wild type, but the growth of invasive hyphae was restricted in host cells (Wilson et al, 2012;Du et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly, for Moarg1, Moarg5,6, and Moarg7, when conidia had been pre-incubated in arginine solution before the plant inoculation assays, exogenous arginine could partially restore the infection defects in appressorial penetration and invasive hyphae growth. The Moarg1, Moarg5,6, and Moarg7 mutants were able to penetrate plant leaf cuticles, but the penetration rate and invasive growth were obviously reduced compared with the wild type, which just like Momet13 and Molys2 mutants of M. oryzae (Yan et al, 2013;Chen et al, 2014). However, studies in str3 (methionine auxotrophy) and Moilv1 (isoleucine auxotrophy) showed that there was no statistical difference in penetration rate between mutants and wild type, but the growth of invasive hyphae was restricted in host cells (Wilson et al, 2012;Du et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the Moarg1 and Moarg5,6 mutants were unable to produce perithecia, and Moarg7 produced few perithecia. Like met13 mutant (methionine auxotrophy) of M. oryzae (Yan et al, 2013), the perithecium production of the Arg − mutants was partially restored via supplementation of oatmeal agar medium with exogenous arginine, which indicated that arginine is required for the sexual reproduction of M. oryzae. Unexpectedly, perithecium production was abolished in the Arg − mutants and wild type, when medium was amended with 2.5 mM arginine.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have shown that several genes involved in fungal metabolism are important to the infection-related morphogenesis and pathogenicity of M. oryzae . Cystathionine beta-lyase (MoStr3) and methylene tetrahydrofolate reductase (MoMet13) affect growth and development processes by regulating methionine biosynthesis (Wilson et al, 2012; Yan et al, 2013). SAICAR synthetase (MoAde1) is required for de novo adenine biosynthesis and pathogenicity (Fernandez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%